Anthelmintic activity of a nanoformulation based on thiophenes identified in Tagetes patula L. (Asteraceae) against the small ruminant nematode Haemonchus contortus - Politi, Flávio Augusto Sanches [UNESP]; Bueno, Renata Vieira; Zeoly, Lucas André; Fantatto, Rafaela Regina [UNESP]; Eloy, Josimar de Oliveira; Chorilli, Marlus [UNESP]; Coelho, Fernando; Guido, Rafael Victório Carvalho; Chagas, Ana Carolina de Souza; Furlan, Maysa [UNESP] (Elsevier, 2021)
The synthesis of thiophenic compounds, previously identified in Tagetes patula, revealed that 4-(5′-(hydroxymethyl)-[2,2′-bithiophene]-5-yl)but-3-yn-1-ol), or simply Thio1, has a pronounced in vitro anthelmintic effect against Haemonchus contortus, showing 100% efficacy in the egg hatch and larval development tests presenting EC50 = 0.1731 mg.mL−1 and EC50 = 0.3243 mg.mL−1, respectively. So, this compound was selected to preparation of a nanostructured formulation to be orally administered to Santa Inês sheep. In general, from the fecal egg count reduction test (FECRT), it was observed that the product kept the parasitic load in the digestive tract of the hosts stable, with eggs per gram of faeces (EPG) counts having a mean value < 3,000 (EPGmean = 2167.1, efficacy = 36,45%), thus protecting the animals from health risks caused by a massive nematode infestation. To better understand the mode of action of this thiophene derivative, in silico molecular modeling studies were carried out with the glutamate-activated chloride channel (GluCl), a well-known molecular target of anthelmintic compounds. Based on the affinity score (GlideScore = -5.7 kcal.mol−1) and the proposed binding mode, Thio1 could be classified as a potential GluCl ligand, justifying the promising results observed in the anthelmintic assays.
Keywords: Docking; French marigold; Gastrointestinal nematode; in vitro; in vivo; UNC-49 receptor